1971
DOI: 10.4141/cjss71-015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Soil Physical Properties on Growth and Manganese, Iron, Aluminum and Molybdenum Content of Oats

Abstract: not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…MacMillan and Hamilton (1971) found that increasing soil temperature decreased the yield but increased the leaf Mn concentration of carrots (Daucus carota L.) grown in the greenhouse. Cheng et al (1971) found the same effects with oats (Avena sativa L.) when comparing root zone temperatures of 21 and 38 C, but these temperatures are likely well above the optimum for growth. Apparently, the growth rate was decreased much more than the Mn uptake rate due to the higher temperature.…”
mentioning
confidence: 71%
“…MacMillan and Hamilton (1971) found that increasing soil temperature decreased the yield but increased the leaf Mn concentration of carrots (Daucus carota L.) grown in the greenhouse. Cheng et al (1971) found the same effects with oats (Avena sativa L.) when comparing root zone temperatures of 21 and 38 C, but these temperatures are likely well above the optimum for growth. Apparently, the growth rate was decreased much more than the Mn uptake rate due to the higher temperature.…”
mentioning
confidence: 71%
“…1973, SIMS andPATRICK 1978). From point of view of the plants the divalent manganese is important, because plants take up manganese mainly as manganous manganese (CHENG and OUELLETTE 1971). According to these points, when the aim is to extract plant-available manganese in the soil the extraction could be carried out with cation exchange resins.…”
Section: Determination Of Exchangeable Manganesementioning
confidence: 99%
“…or AlPO4 suspensions or the addition of a solution of alum, usually potassium alum, to the antigen to form a precipitate in situ. The World Health Organization Technical Report No. 61 (712) indicates that "the expression 'alum-precipitated toxoid' describes a laboratory procedure and in no way defines the nature of the material obtained either quantitatively or qualitatively.…”
Section: Aluminum Adjuvants For Vaccines Andmentioning
confidence: 99%